Reassessing the Perimeter of Government Accounts in China - Mano, Rui (IMF Working Papers; Working Paper ;, 2017)
China's official general government accounts do not include off-budget quasi-fiscal spending unlike the IMF's augmented government accounts. This paper argues that the broader concept of augmented government remains relevant despite recent positive measures to separate off-budget units from the government. In fact, new avenues to finance public infrastructure, such as Special Construction Funds and Government Guided Funds, have emerged and this paper re-defines the perimeter of augmented government to include them. Finally, concrete steps for improving China's fiscal accounts are put forward. If these steps are taken, the perimeter of general government would expand relative to official statistics but would likely be narrower than where augmented aggregates place it.